Understanding Information Retrieval System in the Library of the National Green Tribunal, Eastern Zone Bench, Kolkata: A Case Study - Bagchi, Arindam; Mondal, Parikshit (Internet reference services quarterly, 2021)
Information retrieval is the backbone of an information-serving institution. There is predominant use of printed media in Indian judiciary, as public outreach of the electronic media is still negligible. This work tries to explore the usage of different media of information among users in the library at the National Green Tribunal, Eastern Zone Bench at Kolkata, identify the shortcoming, trace the user's feedback on the Judgment Information System (JUDIS) and improve it. Based on users' responses, a system improvement for information retrieval is suggested, framing an alternative indexing mechanism to improve the proper and accurate search, locally.